Pengaruh Penerapan K3 Terhadap Produktivitas Kerja Melalui Kepuasan Kerja Pada Divisi Produksi PT X - Tangguh Dwi Pramono; Khaerany Aulia; Dewi Sekar Ayu (Bhamada Occupational Health and Safety Environment Journal, 2025)
The number of Work Accident and Death Insurance claims in the last five years has increased significantly. Effective implementation of OHS programs in the company has a positive impact on work productivity. When the risk of accidents and occupational diseases can be properly minimized, it will create a comfortable, safe, and calming work environment for employees that can increase satisfaction. The purpose of this study was to determine the effect of OHS on work productivity through job satisfaction in the Production Division of PT X. The method carried out was quantitative descriptive using SMARTPLS 3.0 with a sample of 105 employees. This study shows that OHS has a positive and significant effect on work productivity. OHS has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on work productivity. The final result of this study is to conclude that job satisfaction has a role as a mediator in the relationship between OHS to work productivity with a partial mediating category.